Agomelatine potentiates anti-nociceptive effects of morphine in a mice model for diabetic neuropathy: involvement of NMDA receptor subtype NR1 within the raphe nucleus and periaqueductal grey - Ozcan, Sibel; Bulmus, Ozgur; Ulker, Nazife; Canpolat, Sinan; Etem, Ebru Onalan; Oruc, Sinem; Ozcan, Mete (Taylor & Francis Ltd, 2020)
Objectives: Opioid analgesics have been used for a long time in the treatment of acute and chronic pain. However, they have many side effects including tolerance development to a significant extent. Agomelatine, an atypical antidepressant, has been demonstrated to be effective in experimental studies on pain. However, the effect of agomelatine on morphine tolerance development and its mechanism of action are unknown. The antinociceptive effects of agomelatine, morphine and their combination were assessed in a mice model for painful diabetic neuropathy. The roles of glutamate ionotropic receptor N-methyl-D-aspartate (NMDA) type subunit-1 (GluN1) in raphe nucleus and periaqueductal gray (PAG) in the effect of agomelatine on neuropathic pain were also investigated in diabetic mice. Methods: Agomelatine (10 mg/kg), morphine (10 mg/kg) and agomelatine + morphine were administered intraperitoneally for 15 consecutive days (twice per day), and the analgesic responses were assessed at days 1, 3, 6, 9, 12 and 15 in healthy and diabetic mice. Real time polymerase chain reaction (RT-PCR) was used to determine the changes in GluN1 expression. Results: The tolerance development for morphine was evident, started at 6th day and remained thereafter, but not for agomelatine. GluN1 in raphe nucleus and PAG was upregulated in morphine treated but not in agomelatine-treated groups. Discussion: The combination of agomelatine with morphine alone causes outlasting analgesic effects of repeated treatment, which can be interpreted as attenuated tolerance. Moreover, we also pointed out for the first time the modulatory effects of agomelatine on GluN1 expression in raphe nucleus and PAG after chronic morphine treatment.
Keywords: Agomelatine; morphine; antidepressant Agents; second generation; chronic Pain; diabetic Neuropathies; drug Tolerance; raphe Nucleus; periaqueductal Gray